Succession of the soil bacterial community as resource utilization shifts from plant residues to rhizodeposits. (October 2022) - Fu, Yingyi; Luo, Yu; Tang, Caixian; Li, Yong; Guggenberger, Georg; Xu, Jianming
Abstract: Identifying the core taxa involved in the utilization of plant straw or/and rhizodeposits is key to understanding the microbial mechanisms underlying the turnover of these plant-derived organic matters, known as the "brown" path and "green" path, respectively. However, this still remains a challenge, primarily due to methodological limitations. By adopting a novel experimental design of parallel 13 C-labelling and DNA-SIP, we identified microorganisms that utilized rhizodeposits and plant straw in soils containing these two plant-derived substances. Additionally, to compare straw utilizers in the soil without plants (straw only) and with plants (straw plus rhizodeposits), we investigated the shift of these substrate-stimulated communities (e.g., straw utilizers) in the presence of live maize plants. Here we showed that i) rhizodeposits were used by a wide range of root-associated microorganisms but plant straw was mainly utilized by oligotrophs, e.g., Arthrobacter, when these two plant-derived substances were co-present; and ii) there was a shift in the bacterial straw utilizer community, e.g., Streptomyces, and their physiological metabolism from saprotrophy to symbiosis when maize plants were present. This study identified distinct utilizers of plant-derived substances, i.e. straw or rhizodeposits, and revealed the shift of soil bacterial community and metabolisms along the autotroph -saprotroph -mutualism continuum. Graphical abstract: Image 1 Highlights: Straw and rhizodeposit utilizers were identified through parallel SIP treatments. Rhizodeposits were utilized by a wide range of root-associated bacteria. Plant straw was mainly utilized by oligotrophs, e.g., Arthrobacter . Bacteria shifted from autotroph or saprotroph to mutualism in planted soil.